New from Old: Advancing Statewide Geophysics with Company Data. Issue 1 (1st December 2019) - Matthews, Sam; Stolz, Edward; Carlton, Astrid
Summary: The Geological Survey of NSW (GSNSW) are the custodians of both government and company geophysical data throughout NSW. The NSW Government has acquired a suite of over 60 airborne magnetic and ground gravity surveys since the 1990s, the data from which has been merged into statewide grids that are delivered, alongside the original survey data, through our web portal 'MinView'. These grids are available for Magnetics, Radiometric, Gravity and Digital Elevation Models. Open-file exploration and mining company data dates back over 60 years, spanning a wide range of conventions, formats, and often missing large amounts of information. GSNSW have committed to a large-scale quality assessment of these data to deliver curated open-file company data to the public via MinView and allow incorporation of good quality company data into the statewide geophysical imagery. This will improve the statewide images because the line spacing of the company surveys is typically much smaller than the regional surveys flown by the government.